The Meso- and Bathypelagic Fishes in a Large Submarine Canyon: Assemblage Structure of the Principal Species in the Gully Marine Protected Area - Kenchington, Trevor John; Themelis, Daphne E.; DeVaney, Shannon Colleen; Kenchington, Ellen Lorraine (Frontiers in Marine Science, 2020)
Midwater trawl surveys were conducted during 2007–10 at meso- and bathypelagic depths in and near The Gully, a large submarine canyon off Nova Scotia that is also a Marine Protected Area. The fish assemblage in the canyon was highly diverse but 20 species together comprised more than 90% of the catch by number and 80% by weight. The most numerous was the gonostomatid Cyclothone microdon while the myctophid Benthosema glaciale was next in number and first in weight. Most of those principal species would be expected in catches taken in oceanic waters beyond the shelf break, only the bottom-spawning Melanostigma atlanticum being, in the surveyed area, distinctively a species of the canyon. Multivariate analyses showed that the primary variations in the assemblage were aligned with drivers that act in open ocean: depth, water mass and both diel and seasonal cycles. However, the effect of the canyon was evident in an up-canyon decline in the catches of most species. We hypothesize that the oceanic species are passively carried into The Gully by the known inflow and are there exposed to intense predation, depleting their numbers. We estimate that biomass flux as sufficient to support the Marine Protected Area’s signature species: northern bottlenose whales (Hyperoodon ampullatus).